(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2025)
The Dumne area forms part of Hawal Massif in the northeastern sector of the Nigerian Basement Complex. The region has experienced multiple phases of tectono-metamorphic deformations denoted as D1, D2 and D3 which have played a significant role in the emplacement of various structural elements and the formation of extensive granitoid bodies. The structural elements are classified into plastic (foliation and lineation), ductile (fold) and brittle (fractures, faults and joints) respectively. They strike dominantly in the N - S (0 - 20o), NNE - SSW (25 – 35o), NE - SW (45 – 55o) and ENE – WSW (65 – 85o) directions as well as minor E-W (90 – 95o) and NW – SE (120 – 150o) directions. The N - S, NNE - SSW and NE - SW are the most dominant and penetrative structures representing a widespread effect of Pan- African orogeny in the area. These structural trends also serve as host to epigenetic vein-type, baryte-fluorite mineralization in the study area. The less dominant ENE - WSW structural trends are pervasive and largely offset in places, suggestive of structures that pre-date the Pan-African events.